2011
DOI: 10.1002/minf.201000097
|View full text |Cite
|
Sign up to set email alerts
|

Growth Response of Trichoderma Species to Organic Solvents

Abstract: The growth response of 25 Trichoderma strains to 26 alkanols and 7 other organic solvents was examined in vitro. The sensitivity of strains considerably varied depending on their taxonomic position, thus the strains of Longibrachiatum section proved to be more tolerant than those of Pachybasium and Trichoderma sections. Significant relationship was revealed between structure of C1 -C24 alkanols and their growth inhibitory effect to Trichodermas, both efficacy and selectivity of C1 -C3 and C14 -C24 alkanols fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Trichoderma spp. have shown greater tolerance for broad spectrum fungicides than many other soil microbes as it has the capacity to colonize the pesticides treated soil more rapidly (Oros et al, 2011). Trichoderma alone or their combinations with bacteria or their immobilized formulations can have great potential, as more than a few unusual contaminants can be treated at the same time and will have wider applicability, hence improving the overall cost effectiveness of the technology.…”
Section: Sensitivity Against Agrochemicalsmentioning
confidence: 99%
“…Trichoderma spp. have shown greater tolerance for broad spectrum fungicides than many other soil microbes as it has the capacity to colonize the pesticides treated soil more rapidly (Oros et al, 2011). Trichoderma alone or their combinations with bacteria or their immobilized formulations can have great potential, as more than a few unusual contaminants can be treated at the same time and will have wider applicability, hence improving the overall cost effectiveness of the technology.…”
Section: Sensitivity Against Agrochemicalsmentioning
confidence: 99%
“…pesticides even in cases, when the active ingredient did not possess fungicidal activity due to toxicity of carriers and surfactants [14] or impurities of liquid carriers. We have tested the shelf life of Trichoderma strains storing their conidia in liquid formulations that meet requirements of application (Table 3).…”
Section: Survival Of Trichodermas In Liquid Formulationsmentioning
confidence: 99%
“…Since discovery of Weidling [1] large Trichoderma based industry has been developed, and diverse ways of their use have been patented (Table 1) as well as several hundred Trichoderma based preparations have been commercialized to prevent yield losses caused by phytopathogenic microbes [11]. These mycofungicides -mostly selected strains of T. harzianum and T. viride -perform well both in laboratory and model applications, but sometimes are less effective in the field where strains must tolerate a wide range of climatic, edaphic and biotic factors [10] [12] [13] [14]. We should remark that some T. harzianum strains seemingly are in reality T. asperellum, thus the taxonomic position of strains needs verification applying recent molecular methods [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In last decade, however, the grave infection has evolved in each season that resulted in disastrous yield losses and led to decrease of harvested area at about 25 %. Series of control measures were tried out, many of them with success with some degree (Børve & Stensvand, 2006;Børve et al, 2010), among them a newly developed biocontrol preparation was applied (Oros & Naár, 2008;Oros et al, 2011). Detailed analysis of weak efficiency of disease control revealed that beside C. gloeosporioides four other anamorphs of Glomerella were present (Table 1), among them C. acutatum (J.H.…”
Section: Introductionmentioning
confidence: 99%